Auschwitz : 1270 to the present - Dwork, Debórah 1954- (Norton, 1996)
Verlagsinfo: More than 1,200,000 dead. This crushing number, the overwhelming scale of the crime, and the vast abandoned site of the ruined chimneys and rusting barbed wire isolate Auschwitz from the rest of the world. This book offers an unprecedented examination of the ties between the ancient market town of Auschwitz and the concentration camp erected in its suburbs. Fully illustrated with over 200 photos, architechtural plans, and historical documents.